PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS BACAAN PADA SISWA KELAS III SD - Diah Pujasari; Asep Samsudin (STKIP Subang, 2022)
This research objective is to improve the ability of reading comprehension toward reading text on the students of third grade at Terang Nusantara Elementary School by using the scramble learning model. The subjects were 17 students in class III C Terang Nusantara Elementary School. This study utilizes Mixed Methods with a Sequential Explanatory design. Sources of data obtained were quantitative data and qualitative data. Quantitative data collection techniques were carried out using the Pretest-Posttest, while qualitative data were obtained using student response questionnaires and observation sheets. The pretest score was 68.32 before applying the scramble learning model. Furthermore, the average posttest score was 82.9 after using the scramble model. Based on the results of the N-gain test, a score of g = 0.56 was obtained in the moderate category. The N-gain effectiveness percentage score of 56.22% indicates a fairly effective interpretation. Based on the results of the study, it can be concluded that the applying of scramble learning model to improve reading comprehension skills of reading texts on third grade students at Terang Nusantara Elementary School is quite effective.